Non-invasive Neuromodulation of Spinal Cord Restores Lower Urinary Tract Function After Paralysis - Gad, Parag N.; Kreydin, Evgeniy; Zhong, Hui; Latack, Kyle; Edgerton, V. Reggie (Frontiers in Neuroscience, 2018)
It is commonly assumed that restoration of locomotion is the ultimate goal after spinal cord injury (SCI). However, lower urinary tract (LUT) dysfunction is universal among SCI patients and significantly impacts their health and quality of life. Micturition is a neurologically complex behavior that depends on intact sensory and motor innervation. SCI disrupts both motor and sensory function and leads to marked abnormalities in urine storage and emptying. Current therapies for LUT dysfunction after SCI focus on preventing complications and managing symptoms rather than restoring function. In this study, we demonstrate that Transcutaneous Electrical Spinal Stimulation for Lower urinary tract functional Augmentation (TESSLA), a noninvasive neuromodulatory technique, can reengage the spinal circuits’ active in LUT function and normalize bladder and urethral sphincter function in individuals with SCI. Specifically, TESSLA reduced detrusor overactivity (DO), decreased detrusor-sphincter dyssynergia (DSD), increased bladder capacity and enabled voiding. TESSLA may represent a novel approach to transform the intrinsic spinal networks to a more functionally physiological state. Each of these features has significant clinical implications. Improvement and restoration of lower urinary tract function after SCI stand to significantly benefit patients by improving their quality of life and reducing the risk of incontinence, kidney injury and urinary tract infection, all the while lowering healthcare costs.